Utilization of machine learning classifiers to predict different forms of mental illness: schizophrenia, PTSD, bipolar disorder and depression - Jaman, Ayman Ibn; Islam, Md.Shehabul; Sakib, Shadman; Khan, Md.Rafin (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.